Respuesta :

For this sys of equations, like all, we first have to solve for y or x in either equation
In this case, lets solve for y in the 2nd equation
-2x+3y=9
add 2x to both sides
3y=9+2x
divide 3 on both sides
y=2/3(x) + 3

now plug in y for the first equation
2x-5(2/3x)+3/11
simplify
-4/3(x) + 3=11
subtract 3 from both sides
-4/3x=8
multiply 3/4 on both sides
x= -6

now plug in x for either equation, lets do the first one again
2 (-6)-5y=11
-5y-12=11
add twelve to both sides
-5y=23
divide
y=-23/5

your final answer would be
x=-6, y=-23/5
ACCESS MORE